Controversial Aspects of the Leasing Contracts Obligations Arising During the Absence of Special Regulation (2019)
The atypicality of the leasing contract, makes its parties face different situations that lack legal certainty, which perhaps due to its contractual nature invites interpretation exercises that may be unfortunate for the proper materialization of the contract. The objective of this work was to reveal some of its vicissitudes generated because of the absence of regulations, in such a way as to provoke in the reader a reflection on how necessary it is to regulate this atypical contract. The methodology used was based on the review of jurisprudence, doctrine, concepts issued by administrative entities and even the practical experience of those who operate with these contracts. As a result, it is suggested the creation of a legislative provision that in an agile way resolves the factual assumptions generating consequences that without it would not be logical.